Thrombectomy for distal medium vessel occlusion stroke: Combined vs. single-device techniques - A systematic review and meta-analysis - Loh, Enver De Wei; Kwok, Gabriel Yi Ren; Toh, Keith Zhi Xian; Koh, Ming Yi; Teo, Yao Hao; Teo, Yao Neng; Chan, Bernard P. L.; Sharma, Vijay Kumar; Ng, Megan Bi-Jia; Lim, Hui Shi; Soon, Betsy; Gopinathan, Anil; et al. (Frontiers in Stroke, 2023)
Background The optimal mechanical thrombectomy technique for acute ischaemic stroke (AIS) caused by distal, medium vessel occlusion (DMVO) is uncertain. We performed a systematic review and meta-analysis evaluating the efficacy and safety of first-line thrombectomy with combined techniques, which entail simultaneous use of a stent retriever and aspiration catheter, vs. single-device techniques, whether stent retriever or direct aspiration alone, for DMVO-AIS patients. Methods We systematically searched the PubMed, Embase and Cochrane CENTRAL databases from inception until 2 September 2022 for studies comparing combined and single-device techniques in DMVO-AIS patients. We adopted the Distal Thrombectomy Summit Group's definition of DMVO. Our outcomes were the modified first-pass effect [mFPE; modified Thrombolysis in Cerebral Infarction (mTICI) 2b-3 at first-pass], first-pass effect (FPE; mTICI 2c-3 at first-pass), successful and complete final reperfusion (mTICI 2b-3 and 2c-3 at end of all procedures, respectively), 90-day functional independence (modified Rankin scale 0-2), 90-day mortality, and symptomatic intracranial hemorrhage (sICH). Results Nine studies were included, with 477 patients receiving combined techniques, and 670 patients receiving single-device thrombectomy. Combined techniques achieved significantly higher odds of mFPE [odds ratio (OR), 2.12; 95% confidence interval (CI), 1.12–4.02; p = 0.021] and FPE (OR, 3.55; 95% CI, 1.97–6.38; p < 0.001), with lower odds of sICH (OR, 0.23; 95% CI 0.06–0.93; p = 0.040). There were no significant differences in final reperfusion, functional independence (OR, 1.19; 95% CI 0.87–1.63; p = 0.658), or mortality (OR, 0.94; 95% CI, 0.50–1.76; p = 0.850). Conclusions In DMVO-AIS patients, mechanical thrombectomy combining stent retrievers and aspiration catheters achieved higher odds of FPE and lower odds of sICH over single-device techniques. There were no differences in functional independence and mortality. Further trials are warranted to establish these findings. Systematic review registration https://www.crd.york.ac.uk/prospero/display_recor d.php?ID=CRD42022370160, identifier: CRD42022370160.